Molecular Identification of Aminoglycoside-Modifying Enzymes and Plasmid-Mediated Quinolone Resistance Genes among Klebsiella pneumoniae Clinical Isolates Recovered from Egyptian Patients - Mohamed F. El-Badawy; Wael M. Tawakol; Shaymaa W. El-Far; Ibrahim A. Maghrabi; Saleh A. Al-Ghamdi; Moselhy S. Mansy; Mohammed S. Ashour; Mohamed M. Shohayeb (International Journal of Microbiology)
Inappropriate use of antibiotics in clinical settings is thought to have led to the global emergence and spread of multidrug-resistant pathogens. The goal of this study was to investigate the prevalence of genes encoding aminoglycoside resistance and plasmid-mediated quinolone resistance among clinical isolates of Klebsiella pneumoniae. All K. pneumoniae isolates were phenotypically identified using API 20E and then confirmed genotypically through amplification of the specific K. pneumoniae phoE gene. All isolates were genotyped by the enterobacterial repetitive intergenic consensus polymerase chain reaction technique (ERIC-PCR). Antibiotic susceptibility testing was done by a modified Kirby-Bauer method and broth microdilution. All resistant or intermediate-resistant isolates to either gentamicin or amikacin were screened for 7 different genes encoding aminoglycoside-modifying enzymes (AMEs). In addition, all resistant or intermediate-resistant isolates to either ciprofloxacin or levofloxacin were screened for 5 genes encoding the quinolone resistance protein (Qnr), 1 gene encoding quinolone-modifying enzyme, and 3 genes encoding quinolone efflux pumps. Biotyping using API 20E revealed 13 different biotypes. Genotyping demonstrated that all isolates were related to 2 main phylogenetic groups. Susceptibility testing revealed that carbapenems and tigecycline were the most effective agents. Investigation of genes encoding AMEs revealed that acc(6′)-Ib was the most prevalent, followed by acc(3′)-II, aph(3′)-IV, and ant(3′′)-I. Examination of genes encoding Qnr proteins demonstrated that qnrB was the most prevalent, followed by qnrS, qnrD, and qnrC. It was found that 61%, 26%, and 12% of quinolone-resistant K. pneumoniae isolates harbored acc(6′)-Ib-cr, oqxAB, and qebA, respectively. The current study demonstrated a high prevalence of aminoglycoside and quinolone resistance genes among clinical isolates of K. pneumoniae.